1999
DOI: 10.1598/rrq.34.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Artifacts as Scaffolds for Genre Development

Abstract: S This study was designed to examine the intersection of genre studies and studies of scaffolded learning. The purpose of the study was to explore children's developing understanding and use of narrative and informational genres, as well as how cultural exemplars functioned to scaffold children's genre development. Using a 3 (grade) by 2 (genre) by 2 (gender) by 2 (task condition) cross‐sectional design, these research foci were investigated by examining stories and biology reports that children wrote in two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 49 publications
1
56
0
3
Order By: Relevance
“…However, as we mentioned previously, in addition to the foundations we present, we have found three recent studies that approach literacy from perspectives that we believe have implications for multicultural educators (Duke, 2000;Kamberelis & Bovino, 1999;Neuman & Celano, 2001). These studies also provide some interesting results when viewed from the Vygotskian concepts and assumptions, especially when we begin to see the links in psychological tools and mediational means to the collective nature of human agency.…”
Section: Mediation Psychological Tools and Mediational Means: The Lsupporting
confidence: 65%
See 2 more Smart Citations
“…However, as we mentioned previously, in addition to the foundations we present, we have found three recent studies that approach literacy from perspectives that we believe have implications for multicultural educators (Duke, 2000;Kamberelis & Bovino, 1999;Neuman & Celano, 2001). These studies also provide some interesting results when viewed from the Vygotskian concepts and assumptions, especially when we begin to see the links in psychological tools and mediational means to the collective nature of human agency.…”
Section: Mediation Psychological Tools and Mediational Means: The Lsupporting
confidence: 65%
“…Our intention is to present salient features from these scholars, three recent studies where literacy and text can be framed as cultural artifacts (Duke, 2000;Kamberelis & Bovino, 1999), and an activity for the multicultural education classroom to make the rich, very applicable concepts that these works provide more accessible. We will rst present the concepts we borrowed as links from the varied, yet closely related, scholarship of Vygotsky and others that have emerged in the past several decades in the West (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This educational speech micro-genre sequentially organizes the culturally recognizable situation of a teacher eliciting a specific response from a student and then evaluating the accuracy of that statement. In this way, speech genres accomplish specific rhetorical tasks in specific communities, reflecting the practices and ideological positions of those communities (Bakhtin 1981;Kamberelis and Bovino 1999).…”
Section: Speech Genresmentioning
confidence: 99%
“…Much of the research on scaffolding (e.g., modeling, demonstrating, prompting, questioning, and joint construction of text) has been conducted with younger children. Kamberelis and Bovino (1999) investigating the role of scaffolding in kindergarten-through second graders' learning of narrative and informational genres, found that most children, especially the younger ones, produced more well-formed texts in the scaffolded condition than the non-scaffolded condition. Wollman-Bonilla and Werchaldo (1999) examined the impact of scaffolding and explicit instruction on children's writing in response to literature, concluding that "repeated modeling, with student participation in constructing the models, may be a powerful instructional tool; explicit instruction may not be as essential as other researchers suggest" (Wollman-Bonilla, 2000, p. 58).…”
Section: Scaffolding and Explicit Instructionmentioning
confidence: 99%